Revitalisasi Tri Pusat Pendidikan dalam Upaya Revolusi Mental - Mu'adz, Muhammad Mush'ab; Purwaningsih, Rahma Fitria (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2023)
The Arabic nation was originally surrounded by two empires that already had civilization, science and one of them had a great heritage in the form of philosophy and wisdom. The two empires are the Roman and the Persian Empire. The Roman Empire was governed by a social system that ignored the human rights of the weak before the strong (rulers). To a certain extent, it is only protecting and giving privileges to the nobles without ignoring the rights of the weak. As there was chaos in Roman society, so it was in Persian society. The conflict between social classes that occurred was no less than what existed in Rome. Even when the Persians were united in sovereignty and political disintegration disappeared, social disintegration continued. So, the true solution to social problems is education which is known by the term Three Education Center. It means that in education there are three elements involved in the educational process, namely family, school, and community. Therefore, the authors try to review more deeply the role of the Three Education Centers as organizers of the mental revolution. The purpose of this writing is to find out the revitalization efforts of the Three Education Centers in the mental revolution effort. The method used is library research, which is in the form of searching for information in books or related scientific articles. The results of the research and conclusions are that in the Three Education Centers, 3 education centers must always be balanced and continuous, namely education at home, education in schools, and education in the community. If it has been carried out, it will undoubtedly create a character, morality, character, and behavior. Abstrak: Bangsa Arab pada awalnya dikelilingi oleh dua imperium yang telah memiliki peradaban, ilmu pengetahuan dan salah satunya menyimpan warisan agung berupa filsafat dan hikmah. Dua imperium itu adalah Kekaisaran Romawi dan Persia. Kekaisaran Romawi diatur oleh suatu sistem sosial yang mengabaikan hak asasi kaum lemah di hadapan kaum yang kuat (penguasa). Dalam batas tertentu hanyalah melindungi dan memberikan hak-hak privilege kepada para bangsawan tanpa mengacuhkan hak-hak kaum lemah. Sebagaimana kekacauan pada masyarakat Romawi, demikian pula terjadi pada masyarakat Persia. Pertentangan antar kelas-kelas sosial yang terjadi tidak lebih kecil dari apa yang ada di Romawi. Sekalipun ketika Persia dapat bersatu dalam kedaulatan dan disintegrasi politik lenyap, akan tetapi disintegrasi sosial terus berlangsung. Maka sejatinya solusi yang tepat problematika sosial ialah pendidikan yang dikenal dengan istilah Tri Pusat Pendidikan. Maksudnya ialah dalam pendidikan terdapat tiga unsur yang terlibat dalam proses pendidikan, yaitu keluarga, sekolah dan masyarakat. Maka dari itu, penulis mencoba mengulas lebih dalam mengenai peran Tri Pusat Pendidikan ini sebagai penyelenggara revolusi mental. Tujuan penulisan ini adalah untuk mencari tahu upaya revitalisasi Tri Pusat Pendidikan dalam upaya revolusi mental. Metode yang digunakan adalah library research berupa pencarian informasi ke buku atau artikel ilmiah terkait. Hasil penelitian dan kesimpulan adalah dalam Tri Pusat Pendidikan terdapat 3 sentral pendidikan yang harus selalu balance dan continue, yaitu pendidikan di rumah, pendidikan di sekolah dan pendidikan di masyarakat. Apabila telah terlaksana, maka niscaya akan tercipta akhlak, moralitas, budi pekerti dan tingkah laku. Kata Kunci: Revitalisasi, Tri Pusat Pendidikan, Revolusi Mental